2010
DOI: 10.1007/s10549-010-0786-2
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols induce apoptosis in breast cancer cell lines via an endoplasmic reticulum stress-dependent increase in extrinsic death receptor signaling

Abstract: Tocotrienols are naturally occurring forms of vitamin E based on their structural similarity. This study focused on investigating anticancer effects of tocotrienols and the mechanisms of apoptosis induction by tocotrienols in vivo and in vitro. Dietary delivery of γ-tocotrienol (γ-T3) suppressed tumor growth in a syngeneic implantation mouse mammary cancer model by inhibiting cell proliferation and inducing apoptosis. In cell culture studies, γ-T3 inhibited colony formation of a mouse mammary cancer cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 57 publications
6
128
4
Order By: Relevance
“…We also discovered that tocotrienol induced DR expression in a non-cell-type-specific fashion that is mediated through reactive oxygen species/ extracellular signal-regulated kinase/p53. Similarly, Park et al (2010) observed that tocotrienol induces apoptosis in breast cancer cell lines via an endoplasmic reticulum stressdependent increase in extrinsic death receptor signaling. However, they found that DR5 induction by tocotrienol was transcriptionally regulated by C/EBP homologous protein.…”
Section: Death Receptors and Tocotrienolmentioning
confidence: 86%
See 2 more Smart Citations
“…We also discovered that tocotrienol induced DR expression in a non-cell-type-specific fashion that is mediated through reactive oxygen species/ extracellular signal-regulated kinase/p53. Similarly, Park et al (2010) observed that tocotrienol induces apoptosis in breast cancer cell lines via an endoplasmic reticulum stressdependent increase in extrinsic death receptor signaling. However, they found that DR5 induction by tocotrienol was transcriptionally regulated by C/EBP homologous protein.…”
Section: Death Receptors and Tocotrienolmentioning
confidence: 86%
“…Park et al (2010) Suppressed preneoplastic mammary epithelial cell proliferation Sylvester et al (2002) Exhibited synergism with erlotinib/gefitinib in suppressing cell proliferation Bachawal et al (2010) Inhibited cell growth irrespective of estrogen receptor status Nesaretnam et al (1998) Exhibited antiproliferation and induced apoptosis by DNA fragmentation McIntyre et al (2000a), McIntyre et al (2000b), Comitato et al (2009) Induced apoptosis in tumor cells through endoplasmic reticulum stress Park et al (2010) Induced apoptosis through TGF-b/Fas/JNK-signaling pathway Shun et al (2004) Reduced PI3K/PDK-1/Akt signaling Sylvester et al (2005) Inhibited cell proliferation and induced apoptosis Shah and Sylvester (2004), Shah and Sylvester (2005b), Sylvester and Shah (2005b), Samant et al (2010) Induced apoptosis through activation of caspases Shah et al (2003), Sylvester and Shah (2005a) Suppressed cell proliferation and down-regulated Bcl-2 and cyclin D1 Hsieh and Wu (2008) Inhibited ER-negative and ER-positive cell proliferation Guthrie et al (1997), Nesaretnam et al (1995) Inhibited proliferation by arresting cell cycle progression Samant et al (2010), Wali et al (2009a) Inhibited tumor cell growth by suppressing HMGR activity Wali et al (2009b) Induced apoptosis through mitochondria-mediated death pathway Takahashi and Loo (2004) Inhibited proliferation through down-regulation of Id1 protein Reduced cell viability and induced apoptosis via the mitochondrial pathway Pierpaoli et al …”
Section: Nf-jb and Tocotrienolmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug resistance is a major clinical limitation for the successful management of breast cancers (42)(43)(44)(45). In the present study, we investigated the mechanisms of TAM-induced apoptosis and drug resistance using MCF-7 cells and its multidrug-resistant variant, MCF-7/ADR cells.…”
Section: Role Of Pkc-erk Signaling In Tamoxifen-induced Apoptosis Andmentioning
confidence: 99%
“…A growing body of studies support that different members of the natural vitamin E family may have unique biological properties relevant to health and disease (Aggarwal et al, 2010). For example, anti-tumorigenic properties of g-tocotrienol, not shared by a-tocopherol, have been described in both breast (Park et al, 2010) and prostate (Kumar et al, 2006) cancer. Furthermore, tocotrienol transport to tissue, including brain, has been reported in the absence of tocopherol transfer protein (TTP), the transport system with high affinity for a-tocopherol (Khanna et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%